Security information resources and strategies of the XXI century - Nagat, Violeta Ioana (Technium Social Sciences Journal, 2020)
National Intelligence is a priority of national security strategies and intelligence to the US security and defence or in the UE States (Strategists/White Books), by which it is proposed, for the first time, achieving an overall, systematic reforms and long term to this area for important strands of which mention: coordination, structural transformations, the formation of a new structureImprove the quality and activity of human resources reform in the intelligence research, technical development capabilities for gathering information. The dynamics of transformations is necessary to streamline the work of intelligence organizations. In Romania there is an older Security Strategy (2006) and no Intelligence strategy, which would need to be developed. Whatever the model and how to design, american or european, for turning his Romanian intelligence is important for their effectiveness by the maximum of the intelligence community and its components. All these directions and actions are required to be prepared for the strategic change in the world and intelligenceul in order to meet the new challenges of the 21st century.